How hemodialysis patients manage dietary and fluid intake? A descriptive qualitative study - Devia Putri Lenggogeni; Hema Malini; Esthika Ariany Maisa; Mahathir Mahathir (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Managing dietary and fluid intake for hemodialysis patients is crucial, but it is also challenging. Non-compliance to diet and fluid intake restriction may increase a patient’s morbidity and mortality. Exploring the experiences of hemodialysis patients who successfully manage those regimens may provide new insight to develop more effective strategies. Purpose: The study aimed to explore the experiences of hemodialysis patients who successfully manage the dietary and fluid intake restrictions. Methods: A descriptive qualitative study was applied. Semi–structured interviews were conducted with 15 hemodialysis patients purposively recruited from a hemodialysis unit of a public hospital in West Sumatera, Indonesia. Interviews were transcribed verbatim and thematically analyzed to describe the phenomenon of hemodialysis patients. The study was reported following the COREQ guidelines. Results: Most participants in this study are female, aged between 38 – 63 years and length of hemodialysis 4 months – 6 years. The finding of this study was that the essential themes that explained how hemodialysis patients adhere to fluid and dietary restrictions are 1) strategies for restricting fluid and dietary intake, 2) motivation to restrict fluid and dietary intake, 3) fear of the effects of non-adherence to fluid and dietary restrictions and 4) social support.